Utilization of cyberspace by terrorist groups and the applicability of the Malaysian law on terrorism - Labanieh, Mohamad Fateh; Zulhuda, Sonny (Asian and African Research Centre (AARC), 2016)
It is an obvious and undeniable fact, that the cyberspace becomes a powerful method which is increasingly and quickly utilized by terrorist organizations to achieve their gruesome and nefarious goals by hitting innocent individuals. This paper has conducted a critical and comprehensive study on the literature review aiming to answer several inquiries about utilization of cyberspace by terrorist groups and the applicability of the Malaysian law on terrorism. The meaning, characteristics and goals of cyber terrorism will be highlighted. Furthermore, this paper will clarify how terrorist groups invade the cyberspace with highlighting on “ISIS” as an example. In addition, this paper will indicate how the Malaysian Law addresses the terrorism. This paper has proved that the terrorist groups become more sophisticated and complex by adopting the cyberspace.